Petrology and contact relationships, SW portion PC Mullen Creek mafic complex, Medicine Bow Mts., Wy. - Edwards, Jeffrey Scott, author; McCallum, M. E. (Malcolm E.), 1934-, advisor; Burns, L. K., committee member; Warren, C. Gerry, committee member (Colorado State University. Libraries, 1983)
Geologic mapping and thin section petrography of rock units in and adjacent to the southwestern portion of the Mullen Creek mafic complex reveals the presence of a roof zone of a Precambrian layered basic intrusion that invaded a metavolcanic sequence (predominantly hornblende gneiss). This portion of the mafic complex consists of variably metamorphosed interlayered rocks that originally ranged from pyroxenite to anorthosite but were dominantly gabbro and leucogabbro. Most of these rocks underwent regional medium-grade metamorphism to form amphibolite facies assemblages in which hornblende has replaced pyroxene, labradorite has remained stable and relict igneous textures are preserved. A later episode of retrogressive low-grade metamorphism has produced locally abundant fractures, veinlets and minerals typical of the greenschist facies such as chlorite, epidote, talc, serpentine and saussurite.
Zip file contains supplementary plates 1 and 2.
Keywords: southern Wyoming; Medicine Bow Mountains; Prospect Mountain granite; Big Creek shear zone; layered mafic intrusion; Mullen Creek-Nash Fork shear zone; Mullen Creek mafic complex; northern Colorado; hornblende gneiss; Petrology -- Medicine Bow Mountains (Colo. and Wyo.)